2016
DOI: 10.1159/000452130
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Osteocalcin and Polymorphisms of<b> </b>the<b><i> Osteocalcin</i></b> Gene with Bone Mineral Density in Postmenopausal and Elderly Chinese Women

Abstract: Background: The aims of this study were: (1) to evaluate the association of serum osteocalcin with bone mineral density (BMD) and markers of bone metabolism in postmenopausal and elderly Chinese women, and (2) to observe the relationships of single-nucleotide polymorphisms (SNPs) in and around the osteocalcin gene with osteocalcin and BMD. Methods: A cross-sectional study was conducted with 725 postmenopausal Chinese women. Five SNPs (rs1543294, rs1800247, rs759330, rs2842880, and rs933489) of the osteocalcin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Osteocalcin can bind strongly to hydroxyapatite to bridge the matrix and mineral fractions of bone tissue [ 45 ]. Serum levels of osteocalcin have been proven to be closely related to the bone formation rate [ 46 ], and they are positively correlated with serum P levels [ 47 ], which is consistent with the findings of this study, suggesting that bone formation could be improved in the MCP group. Previous studies showed that phosphorus-deficient diets could reduce bone formation to maintain serum levels of Ca and P in lactation cows [ 48 ] and decrease the serum osteocalcin levels in growing–finishing pigs [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Osteocalcin can bind strongly to hydroxyapatite to bridge the matrix and mineral fractions of bone tissue [ 45 ]. Serum levels of osteocalcin have been proven to be closely related to the bone formation rate [ 46 ], and they are positively correlated with serum P levels [ 47 ], which is consistent with the findings of this study, suggesting that bone formation could be improved in the MCP group. Previous studies showed that phosphorus-deficient diets could reduce bone formation to maintain serum levels of Ca and P in lactation cows [ 48 ] and decrease the serum osteocalcin levels in growing–finishing pigs [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Last but not least, the carboxylation status of sOC was not mentioned in any of the included studies. As a matter of fact, both OC and unOC in the circulation have been reported to correlate with each other [37, 38] and with bone quality [39, 40] but most of the conventional sOC assay kits are designed for total sOC while unOC can only be evaluated with special techniques [41, 42]. The result of this meta-analysis might not be significantly influenced by the carboxylation status of sOC as the same OC assay kit was adopted in PMO and control groups within each individual study.…”
Section: Discussionmentioning
confidence: 99%
“…When Lumachi et al [ 12 ] evaluated BAP along with other bone formation markers (osteocalcin, type I collagen and BMD) in elderly men with no history of fractures, they found no relationship at all between BAP and bone density in this population. In a similar comparison among elder Chinese women, Zhang et al [ 20 ] found a positive correlation between osteocalcin and BAP but a negative correlation with total and subregional BMD (at lumbar spine and total hip), suggesting that osteocalcin gene variants may not contribut to BMD in postmenopausal and elderly Chinese women. Those authors also found that BAP was a useful parameter for evaluating age-related changes in bone turnover.…”
Section: Discussionmentioning
confidence: 99%